-2x-6=-2x-4

Simple and best practice solution for -2x-6=-2x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-6=-2x-4 equation:


Simplifying
-2x + -6 = -2x + -4

Reorder the terms:
-6 + -2x = -2x + -4

Reorder the terms:
-6 + -2x = -4 + -2x

Add '2x' to each side of the equation.
-6 + -2x + 2x = -4 + -2x + 2x

Combine like terms: -2x + 2x = 0
-6 + 0 = -4 + -2x + 2x
-6 = -4 + -2x + 2x

Combine like terms: -2x + 2x = 0
-6 = -4 + 0
-6 = -4

Solving
-6 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2.39=x-40 | | 10+9C+5C*2-4+6C= | | a-2-2+15=1+3a | | 49h+20=314 | | -2x-6=-2-4 | | 4p+2+2p+1=8 | | -5x+9=17-x | | 6y=8x-10 | | 10t^2=12t+23 | | C+c=73 | | -3(-4-6y)+7(y+5)= | | 75+2x=0-15 | | 4+x=200 | | 4x^2+4x+32=0 | | 4x+1+3x=-3 | | 2x^2+3+3=-7x | | Y=2x+(-8) | | -15x+9=17-x | | 4X-8=3(2X-4) | | 75+2x=15 | | X+2=2overy-1 | | +t/12=-3 | | -6b+28=9b-2 | | 3x-9=4x-24 | | 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 |

Equations solver categories